Natural Hazards Impacts, Adjustments and Resilience - Noroozinejad Farsangi, Ehsan (IntechOpen, 2021)
Natural Hazards - Impacts, Adjustments, and Resilience is a collection of chapters on recent developments as well as problems of current interest in the field of natural hazards by academicians, researchers, and practicing engineers from all over the world. It includes seventeen chapters and encompasses multidisciplinary areas within the areas of natural hazards such as resilience, reliability, crisis management, risk analysis, and simulations. This book is a useful reference for undergraduate and postgraduate students, academicians, and researchers across a variety of engineering disciplines as well as practicing engineers.